2022
DOI: 10.1101/2022.06.21.497104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arginine methylation of Puf4 drives diverse protein functions

Abstract: The evolutionarily conserved Pumilio domain-containing RNA binding proteins (RBPs) are involved in many steps of post-transcriptional gene regulation, including RNA stability, polyadenylation, deadenylation, and translation. RBPs are post-translationally modified by methylation of arginine/glycine-rich domains, though the consequences of these modifications are not well known. We determined the arginine methylation and phosphorylation landscape of the Pumilio domain-containing RBP Puf4 from the basidiomycete f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…RNA interactions of Puf4 involve genes required for cell wall synthesis, drug resistance, as well as regulating gene expression. More importantly, Puf4 immuno-precipitation also revealed a direct interaction with Ago1 (K alem et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA interactions of Puf4 involve genes required for cell wall synthesis, drug resistance, as well as regulating gene expression. More importantly, Puf4 immuno-precipitation also revealed a direct interaction with Ago1 (K alem et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We also identified that deletion of Puf4 results in enhanced silencing by approximately three-fold and this is the first gene whose mutation has been identified to enhance silencing. Puf4 belongs to the Pumilio and Fem-3 (PUF) family of mRNA binding factors and has been shown to bind to several RNAs in C. neoformans (KALEM et al 2021;KALEM et al 2022). RNA interactions of Puf4 involve genes required for cell wall synthesis, drug resistance, as well as regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation